Interactive Learning Software for Engineering Subjects Based on MATLAB-GUI - Naim, Nani Fadzlina; Sarnin, Suzi Seroja; Abdul Rahman, Husna; Osman, Nurul Falah; W. Muhamad, Wan Norsyafizan; Yaacob, Norsuzila (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2016)
This paper presents the development and application of interactive learning software for communication engineering subjects. Currently, the software consists of two interactive communication engineering subjects; electromagnetic and digital signal processing (DSP). The software is developed using MATLAB R2014a and its Graphic User Interface (GUI). By using this software, students are able to understand the subjects well as it shows the required value automatically and it also displays the appropriate plots. This software is also suitable to be used as a teaching aid for the lecturers. The standalone program is also developed such that user does not need to install MATLAB in order to use this interactive learning software.